An Infected, Noncoronary, Bare Metal Stent Presenting as a Right Groin Abscess - Madiha Khan; Youssef Mourad; Alan Zeitlin; Martine Alice Louis; Syed Ali Rizvi; Kelly L. Cervellione (Case Reports in Vascular Medicine)
Bare metal stent infections complicating peripheral endovascular stenting are rare but can be associated with devastating morbidities. The current standard of care necessitates explantation and extra-anatomical bypass of the affected limb. We report the case of a patient presenting with a right groin abscess with draining sinuses secondary to an infected common femoral and right external iliac artery bare metal stent. In addition, a portion of the stent was explanted into the subcutaneous tissues instead of where it was placed intravascularly one year prior. The patient was not an ideal candidate for explantation and bypass due to significant medical comorbidities and underwent local debridement and long-term antibiotic management instead. His postoperative course was uncomplicated, and he had a successful outcome with management utilizing antibiotics and debridement. We aim to highlight the importance of recognizing bare metal stent infections along with their deceptive cutaneous manifestations in order to prevent the development of significant morbidity and mortality.